Robust neurocognitive individual differences in grammatical agreement processing: A latent variable approach - Tanner, Darren (Cortex, 2019)
Many neurocognitive accounts of language processing presume that neural responses detected in grand mean analyses of cortical electrophysiological activity reflect the normative brain response in the population under investigation. However, emerging work now shows that individuals' brain responses can vary systematically in both the size and type of effect elicited. The present research therefore examined individual differences in neural activity elicited by grammatical agreement anomalies during language comprehension in a large cohort of highly literate, monolingual English speakers (N = 114), a population generally assumed to be relatively homogenous in terms of linguistic knowledge and processing. Results showed systematic variability in event-related brain potentials (ERPs) elicited by subject-verb agreement anomalies, with brain responses varying on a continuum between N400 and P600 dominant responses. Similar variation was found both when agreement was realized via inflectional morphology or via lexical alternations. Individuals' brain response type correlated strongly across these two conditions. Similar variation was also found for ERPs elicited during rapid serial visual presentation and when self-paced ERPs were recorded. Multilevel latent variable regression showed that variation in brain response amplitude and type was not related to individual differences in language experience or verbal working memory capacity, despite high statistical power. These findings indicate that descriptions of processing dynamics predicated solely on grand mean analyses of central tendency can fail to provide an accurate, generalizable account of how processing unfolds in many or most individual members of the population studied. Furthermore, these findings show that systematic individual variation in engagement of neural system supporting grammatical processing is found even in language users at the highest end of the proficiency spectrum and in grammatically simple sentences. This study therefore has implications for studies of language processing in atypical populations.